2010
DOI: 10.2147/nds.s10974
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-lowering phytosterols: factors affecting their use and efficacy

Abstract: Phytosterols are essential components of plant cells and therefore naturally present in the human diet. When used therapeutically, phytosterols can significantly lower serum cholesterol concentrations. Meta-analyses of clinical trials indicate about 10% reduction of low-density lipoprotein cholesterol when phytosterols are consumed at the recommended dose of 2 g/d. Thus, phytosterols can be an important part of an overall dietary strategy to manage cholesterol levels, particularly for patients who cannot toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 162 publications
(147 reference statements)
0
16
0
3
Order By: Relevance
“…The primary mechanism by which phytosterols lower cholesterol is thought to be displacement of cholesterol from micelles by free phytosterols [32] and phytosterols hydrolyzed from phytosterol esters [33]. We recently observed that about 90% of phytosterol oleate esters are hydrolyzed in vivo (unpublished observa- Values are means ± SEM; n = 9 to 10.…”
Section: Discussionmentioning
confidence: 99%
“…The primary mechanism by which phytosterols lower cholesterol is thought to be displacement of cholesterol from micelles by free phytosterols [32] and phytosterols hydrolyzed from phytosterol esters [33]. We recently observed that about 90% of phytosterol oleate esters are hydrolyzed in vivo (unpublished observa- Values are means ± SEM; n = 9 to 10.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological studies of triterpenoids showed anticancer, anti-inflammatory, anti-ulcerogenic, anti-microbial, anti-viral (including anti-HIV), anti-fungal, analgesic, antioxidative, hepatoprotective and some other activities [3][4][5][6][7][8][9][10]. Phytosterols are well known for their cholesterol-lowering properties, and also demonstrate anticancer, anti-inflammatory and immunoregulatory activities [11,12]. Due to the growing interest in triterpenoids and phytosterols, the development of suitable modern analytical methods for the determination of these metabolites in natural products, is of paramount importance.…”
Section: Introductionmentioning
confidence: 99%
“…Phytosterol, consumed with the diet, can influence cholesterol metabolism and the main health‐promoting effect is lowering of serum cholesterol . It has been demonstrated that although tetraploid and hexaploid wheat sterol profiles were qualitatively the same, they differed significantly on the basis of the relative amounts of specific compounds …”
Section: Introductionmentioning
confidence: 99%
“…16 Phytosterol, consumed with the diet, can influence cholesterol metabolism and the main health-promoting effect is lowering of serum cholesterol. 17 It has been demonstrated that although tetraploid and hexaploid wheat sterol profiles were qualitatively the same, they differed significantly on the basis of the relative amounts of specific compounds. 18,19 In several countries primitive wheats also represent the basis for the manufacture of local foods that are now being revalued after a long period of neglect.…”
Section: Introductionmentioning
confidence: 99%